Aleksandram Zāmelim - 125 - Jamonte, Daiga; Kuzņecova, Kristīne; Latvijas Universitātes Muzejs (My University, 2022)
Latviešu botāniķa un ģenētiķa Aleksandra Zāmeļa (1897-1943) 125. jubilejai veltīta Latvijas Universitātes Muzeja virtuālā izstāde “Aleksandram - Zāmelim 125”.

A virtual exhibition “Aleksandram Zāmelim - 125” of the Museum of the University of Latvia is dedicated to the 125th anniversary of the Latvian botanist and geneticist Aleksandrs Zāmelis (1897-1943).
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science; Aleksandrs Zāmelis; botānika; ģenētika; biogrāfija